Direct-PCR from rectal swabs and environmental reservoirs: a fast and efficient alternative to detect blaOXA-48 carbapenemase genes in an Enterobacter cloacae outbreak setting - Probst, Katja; Boutin, Sébastien; Späth, Isabel; Scherrer, Martin; Henny, Nicole; Sahin, Delal; Heininger, Alexandra; Heeg, Klaus; Nurjadi, Dennis (Environmental research, 2022)
Carbapenemase-producing bacteria are a risk factor in clinical settings worldwide. The aim of the study was to accelerate the time to results during an outbreak situation with blaOXA-48-positive Enterobacter cloacae by using a real-time multiplex quantitative PCR (qPCR) directly on rectal swab specimens and on wastewater samples to detect carbapenemase-producing bacteria. Thus, we analyzed 681 rectal swabs and 947 environmental samples during a five-month period by qPCR and compared the results to culture screening. The qPCR showed a sensitivity of 100% by testing directly from rectal swabs and was in ten cases more sensitive than the culture-based methods. Environmental screening for blaOXA-48-carbapenemase genes by qPCR revealed reservoirs of different carbapenemase genes that are potential sources of transmission and might lead to new outbreaks. The rapid identification of patients colonized with those isolates and screening of the hospital environment is essential for earlier patient treatment and eliminating potential sources of nosocomial infections.
Available online 31 July 2021
Im Titel Zusatz zum Titel ist "OXA-48" tiefgestellt
Gesehen am 18.11.2021